Application of a novel molecular method to age free‐living wild Bechstein's bats. (27th July 2018) - Wright, Patrick G. R.; Mathews, Fiona; Schofield, Henry; Morris, Colin; Burrage, Joe; Smith, Adam; Dempster, Emma L.; Hamilton, Patrick B.
Abstract: The age profile of populations fundamentally affects their conservation status. Yet, age is frequently difficult to assess in wild animals. Here, we assessed the use of DNA methylation of homologous genes to establish the age structure of a rare and elusive wild mammal: the Bechstein's bat ( Myotis bechsteinii ). We collected 62 wing punches from individuals whose ages were known as a result of a long‐term banding study. DNA methylation was measured at seven CpG sites from three genes, which have previously shown age‐associated changes in humans and laboratory mice. All CpG sites from the tested genes showed a significant relationship between DNA methylation and age, both individually and in combination (multiple linear regression R 2  = 0.58, p  < 0.001). Despite slight approximation around estimates, the approach is sufficiently precise to place animals into practically useful age cohorts. This method is of considerable practical benefit as it can reliably age individual bats. It is also much faster than traditional capture–mark–recapture techniques, with the potential to collect information on the age structure of an entire colony from a single sampling session to better inform conservation actions for Bechstein's bats. By identifying three genes where DNA methylation correlates with age across distantly related species, this study also suggests that the technique can potentially be applied across a wide range of mammals.